2015
DOI: 10.1136/bmjopen-2015-009715
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate prescribing (PIP) in long-term care (LTC) patients: validation of the 2014 STOPP-START and 2012 Beers criteria in a LTC population—a protocol for a cross-sectional comparison of clinical and health administrative data

Abstract: IntroductionPotentially inappropriate prescribing (PIP) is frequent and problematic in older patients. Identifying PIP is necessary to improve prescribing quality; ideally, this should be performed at the population level. Screening Tool of Older Persons’ potentially inappropriate Prescriptions/Screening Tool to Alert doctors to Right Treatment (STOPP/START) and Beers criteria were developed to identify PIP in clinical settings and are useful at the individual patient level; however, they are time-consuming an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The predictive validity of the STOPP criteria was recently shown slightly outperforming the Beers criteria to detect adverse drug events, but definitive evidence is still lacking . Hopefully, prospective randomized studies that are currently ongoing could clarify the matter definitely . Finally, we recognize the lack of collecting any parameter measuring social and clinical impacts.…”
Section: Discussionmentioning
confidence: 97%
“…The predictive validity of the STOPP criteria was recently shown slightly outperforming the Beers criteria to detect adverse drug events, but definitive evidence is still lacking . Hopefully, prospective randomized studies that are currently ongoing could clarify the matter definitely . Finally, we recognize the lack of collecting any parameter measuring social and clinical impacts.…”
Section: Discussionmentioning
confidence: 97%
“…Residents in LTC facilities use more drugs than those in the community because they tend to be older, more frail and sicker than seniors living in the community. 6,53,54 This increased drug use continues even after adjusting for clinical characteristics. 55 An Ontario study found that, on average, younger LTC residents used more drugs than older LTC residents and that there was high variation in the number of drugs used by LTC residents across facilities.…”
Section: Number Of Drugs Prescribedmentioning
confidence: 99%
“…Evaluating PIM use can reduce ADEs and the incidence of hospitalization among older adults. 27 The current approach used to manually assess PIM use is timeconsuming and difficult to be generalized. The rapid assessment tool designed in this study may enable pharmacists to rapidly screen PIMs during the implementation of medication integration.…”
Section: Discussionmentioning
confidence: 99%